The tensile capacity of suction caissons in sand under rapid loading - Houlsby, G; Kelly, R; Byrne, B (2005)
We develop here a simplified theory for predicting the capacity of a suction caisson in sand, when it is subjected to rapid tensile loading. The capacity is found to be determined principally by the rate of pullout (relative to the permeability of the sand), and by the ambient pore pressure (which determines whether or not the water cavitates beneath the caisson). The calculation procedure depends on first predicting the suction beneath the caisson lid, and then further calculating the tensile load. The method is based on similar principles to a previously published method for suction-assisted caisson installation (Houlsby and Byrne 2005). In the analysis a number of different cases are identified, and successful comparisons with experimental data are achieved for cases in which the pore water either does or does not cavitate. © 2005 Taylor and Francis Group.